Phytoremediation Potential of Iris spp. - Ioana CRIȘAN; Roxana VIDICAN; Anca PLEȘA; Tania MIHĂIESCU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2021)
Iris plants are widely cultivated flowering ornamentals, with a long history of traditional use in Eurasia, where this genus is reaching the highest diversity. This paper aims to provide an overview on recent advances related to the phytoremediation potential of plants from the genus Iris, in order to promote the use of these species in phytoremediation programs. According to the relevant literature, eight species from genus Iris present phytoremediation potential (I. dichotoma, I. germanica, I. halophila, I. lactea, I. latifolia, I. pseudacorus, I. sibirica, I. wilsonii). The studies addressed potential of plants to mitigate toxic metals/metalloids (As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Zn), excess of nutrients (P, N), pesticides, petroleum hydrocarbons, pharmaceuticals as well as dyes. Most studies focused on wastewater treatment and environments contaminated due to mining activities. Main hindrances in upscaling this green technology remain mitigation of toxicity stress in plants during remediation and the disposal of resulting contaminated biomass. In this sense, use of beneficial microorganisms to alleviate phytotoxicity effects and new valorization possibilities of contaminated Iris spp. biomass have been proposed recently. Designing an entire cycle that includes phytoremediation and sustainable value chains for contaminated biomass could prove feasible and should receive more attention.